Effect of the inoculation of sulfur amino acids and vitamin b9 on the degree of feathering of broilers - Reina Rodriguez, Daniel Felipe; Gamboa González, Nidia Fernanda; Caicedo Blanco, Yuly Andrea (Spei Domus, 2022)
The fledging process of the birds begins from day 9 of incubation where the formation of the follicles can already be evidenced and by day 11 the formation of down is already evident. The effect of in ovo inoculation of sulfur amino acids (ASA) and vitamin B9 on the degree of feathering in broilers was evaluated, the study had a duration of 62 days (21 days of incubation and 42 days of life). A total of 1200 fertile eggs from 41-week-old broiler breeders were used, divided into five treatments (n=240). T1: no inoculation. T2: saline solution (NaCl 0.75%), T3: vitamin B9, T4: ASA and T5: combination of vitamin B9 + ASA. The degree of feathering was carried out on days 28, 35 and 42 of age; the comparison of the means was carried out by means of the SNK test using the statistical program R. With a significance of 5 %. No significant differences were observed in the variables analyzed through the life phases of the birds (p>0.05). The doses of the substances used in the inoculation did not influence the degree of fledging of the birds. The inoculation of these nutrients individually and associated with folic acid in the embryonic phase did not influence this morphological characteristic
Keywords: Inoculation; Folic Acid; Sulfur Amino Acids; Vitamin B9; In Ovo